Employing scientific evidence through synthetic indices to support management and conservation policies for an endangered tree of the Gran Chaco - Camps, Gonzalo Andres; Cosacov, Andrea; Verga, Anibal; Sérsic, Alicia N. (Elsevier, 2025)
Management and conservation programs require accessible scientific evidence to effectively plan and achieve their goals. Facing regional and species-specific threats, Gonopterodendron sarmientoi, an endangered tree native to the Gran Chaco region, requires scientific evidence to support management and conservation actions, notably in forest management and territorial planning. To bridge this crucial gap, we developed indices that integrate genetic, evolutionary, morphological, threat-related, and ethnobotanical data concerning G. sarmientoi at a landscape level. Across twenty-four localities of this species, we have created four distinct indices. The first index amalgamates data on genetics, functional traits, and paleoclimate information. The second index incorporates data on threats stemming from deforestation and climate change scenarios. The third index provides supplementary insights into the species’ utilization by indigenous groups. Finally, the fourth index combines all the aforementioned data to prioritize the most valuable and threatened localities. Through this comprehensive approach, we have identified specific in-situ and ex-situ management and conservation actions for G. sarmientoi. This approach considers broader-scale conservation efforts and considers large-scale variations and processes. The indices effectively link scientific data with actionable insights, providing decision-makers involved with G. sarmientoi with concise information that encapsulates the most pertinent aspects of species conservation.